Synthesis, Characterization, and Perfumery Application of Acetal Derivatives of 2-Methyl-3-(4-R-Phenyl) Propanal: A Short Review - Mohd Alif Haikal Ahmad Mazahar; Juliana Jumal (USIM Press, 2024)
VOL. 9 NO. 1 (2023) Page (1-11)